Cells on the move: Modulation of guidance cues during germ cell migration. Issue 3 (3rd July 2017) - Deshpande, Girish; Barr, Justinn; Gerlitz, Offer; Lebedeva, Lyubov; Shidlovskii, Yulii; Schedl, Paul
ABSTRACT: In Drosophila melanogaster the progenitors of the germ-line stem cells, the primordial germ cells (PGCs) are formed on the outside surface of the early embryo, while the somatic gonadal precursor cells (SGPs) are specified during mid-embryogenesis. To form the primitive embryonic gonad, the PGCs travel from outside of the embryo, across the mid-gut and then migrate through the mesoderm to the SGPs. The migratory path of PGCs is dictated by a series of attractive and repulsive cues. Studies in our laboratory have shown that one of the key chemoattractants is the Hedgehog (Hh) ligand. Although, Hh is expressed in other cell types, the long-distance transmission of this ligand is specifically potentiated in the SGPs by the hmgcr isoprenoid biosynthetic pathway. The distant transmission of the Hh ligand is gated by restricting expression of hmgcr to the SGPs. This is particularly relevant in light of the recent findings that an ABC transporter, mdr49 also acts in a mesoderm specific manner to release the germ cell attractant. Our studies have demonstrated that mdr49 functions in hh signaling likely via its role in the transport of cholesterol. Given the importance of cholesterol in the processing and long distance transmission of the Hh ligand, this observation has opened up an exciting avenue concerning the possible role of components of the sterol transport machinery in PGC migration.